Serum artemin is not correlated with sensitivity within dogs with naturally occurring osteoarthritis pain - Ankita Gupta (Nature Portfolio, 2021)
Abstract Osteoarthritis (OA) pain is associated with peripheral and central sensitization in humans and results in widespread increased sensitivity across the body. Sensitization contributes to the OA-associated pain (OAP) state. We recently identified increased levels of an endogenous neurotrophic factor, artemin (ARTN), in dogs with OAP compared to healthy pain-free controls. Circulating ARTN released from damaged tissues in OA, may play a central role in widespread sensitivity and pain. However, the relationship between ARTN and somatosensory sensitivity remains unknown. The study aimed to assess the relationship between serum ARTN concentrations and measures of sensitivity in dogs with OAP using quantitative sensory testing. We hypothesized that there would be a positive association between circulating ARTN and increased sensitivity to mechanical and thermal stimuli in dogs with OAP. We used linear and logistic regression models to assess the relationship between ARTN, sensitization, and pain within a cohort of 43 dogs with spontaneous OAP. Serum ARTN was not associated with the degree of sensitization within dogs with OAP. Further, across dogs with varying OAP severity, we did not find any association between ARTN, and clinical measures of joint pain and disability. Although a relationship between ARTN and joint pain was not ruled out.